IJCM_229A: A Community-based screening programme for oral, breast, and cervical cancer in the rural area of Dakshin Kannada - Saraswathy M V; Unnikrishnan Bhaskaran; Rekha T; Kumar Nithin; Rao Mithun; Mithra Prasanna; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Karnataka recorded 87304 new cancer cases in the year 2021. Breast, lip and oral cavity, cervix were the top cancer sites amongst all sexes and are preventable. Despite the nation-wide launch of Population-based screening (PBS) in 2016, the reported coverage of individuals who were screened for these three cancers in Dakshin Kannada was 0.4% (NFHS-5). The study introduces on-site screening for oral and breast cancer in the community. Objectives: To estimate the proportion of pre-cancerous lesions of oral, breast, and cervical cancer, through community-based screening in adults aged 18 to 65 years, in the catchment area of a medical college in Dakshina Kannada Methodology: This observational study was conducted among all persons aged 18 to 65years, residing in the rural catchment area of a medical college in Mangalore taluk of Dakshina Kannada and consenting for the study. Pregnant women and persons with prior diagnosis of oral, breast or cervical cancer were excluded. Two-stage cluster sampling was used to enrol an estimated sample of 1120 beneficiaries. The study comprised of house-to-house survey, cancer awareness sessions, and community-based screening. Screening tests included Oral visual examination, clinical breast examination, iBreast examination (iBE; electronic palpation by ibreast device), and Pap smear tests. Participants who screened positive were referred for diagnostic tests and management. Results: The study was completed with survey of 556 households, 3 cancer awareness sessions, and screening of 525 beneficiaries (325 females and 200 males) for oral, breast, and cervical cancer. Three participants screened positive for oral cancer, and one participant for breast cancer, who were referred for management to tertiary care hospital attached to the medical college. 25% of female participants underwent cervical cancer screening, with no one detected with pre-cancerous lesions. Conclusion: A combination of house-to-house and camp-based approaches along with awareness sessions results in improved coverage of PBS in the community.